2012
DOI: 10.1016/j.juro.2012.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Improvement of Renal Function After Pyeloplasty in Pediatric Patients: A Prospective Study

Abstract: Sonographic and urinary biochemical parameters may predict improvement in renal function after pyeloplasty. Pelvic anteroposterior diameter, pelvic cortical ratio and pelvic urine protein-to-creatinine ratio are the most useful parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In the present study, large APD and thin PT during non-pain periods are associated with impaired renal function in patients with hydronephrosis and abdominal pain, which is consistent with previous studies in asymptomatic UPJO patients [12][13][14]. Acute pain attacks have been shown to be linked to worsening DRF.…”
Section: Apd and Ptsupporting
confidence: 92%
“…In the present study, large APD and thin PT during non-pain periods are associated with impaired renal function in patients with hydronephrosis and abdominal pain, which is consistent with previous studies in asymptomatic UPJO patients [12][13][14]. Acute pain attacks have been shown to be linked to worsening DRF.…”
Section: Apd and Ptsupporting
confidence: 92%
“…Previous reports stated that percent improvement in anteroposterior diameter and postoperative pelvic anteroposterior diameter measurements can predict success after pyeloplasty [4]. Chipde et al [19 ]confirmed that pelvic anteroposterior diameter and PCR can be useful parameters for the prediction of successful intervention. …”
Section: Discussionmentioning
confidence: 97%
“…A series of studies by Chipde et al (10) and Longpre et al (11) showed that a high percentage of patients after pyeloplasty avoided diuretic isotope renography if the ultrasound parameters did not get worse. This issue can save time and money and avoid infections caused by catheterization for scanning and radiation from the follow-up scan.…”
Section: Discussionmentioning
confidence: 99%